Autophagy, Inflammation, and Metabolism (AIM) Center in its second year. Issue 10 (3rd October 2019) - Deretic, Vojo; Prossnitz, Eric; Burge, Mark; Campen, Matthew J.; Cannon, Judy; Liu, Ke Jian; Liu, Meilian; Hall, Pamela; Sklar, Larry A.; Allers, Lee; Mariscal, Luisa; Garcia, Sally Ann; et al.
ABSTRACT: The NIH-funded center for autophagy research named Autophagy, Inflammation, and Metabolism (AIM) Center of Biomedical Research Excellence, located at the University of New Mexico Health Science Center is now completing its second year as a working center with a mission to promote autophagy research locally, nationally, and internationally. The center has thus far supported a cadre of 6 junior faculty (mentored PIs; mPIs) at a near-R01 level of funding. Two mPIs have graduated by obtaining their independent R01 funding and 3 of the remaining 4 have won significant funding from NIH in the form of R21 and R56 awards. The first year and a half of setting up the center has been punctuated by completion of renovations and acquisition and upgrades for equipment supporting autophagy, inflammation and metabolism studies. The scientific cores usage, and the growth of new studies is promoted through pilot grants and several types of enablement initiatives. The intent to cultivate AIM as a scholarly hub for autophagy and related studies is manifested in its Vibrant Campus Initiative, and the Tuesday AIM Seminar series, as well as by hosting a major scientific event, the 2019 AIM symposium, with nearly one third of the faculty from the International Council of Affiliate Members being present and leading sessions, giving talks, and conducting workshop activities. These and other events are often videostreamed for a worldwide scientific audience, and information about events at AIM and elsewhere are disseminated on Twitter and can be followed on the AIM web site. AIM intends to invigorate research on overlapping areas between autophagy, inflammation and metabolism with a number of new initiatives to promote metabolomic research. With the turnover of mPIs as they obtain their independent funding, new junior faculty are recruited and appointed as mPIs. All these activities are in keeping with AIM's intention to enable the next generation of autophagy researchers and help anchor, disseminate, and convey the depth and excitement of the autophagy field.